Method and device for representing migration capability of silver element in glass

Through salt bath treatment and scanning electron microscopy analysis, the diffusion coefficient and diffusion layer thickness of silver elements in photosensitive microcrystalline glass are characterized, which solves the problem of failure to effectively characterize silver migration ability in the prior art, and provides the nucleation process of photosensitive microcrystalline glass Research supports the application of glass materials with different network structures.

CN119269562APending Publication Date: 2025-01-07CDGM GLASS LLC
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411354829.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The prior art has failed to effectively characterize the migration ability of silver elements in photosensitive microcrystalline glass, which has affected the nucleation process and final performance of glass. Especially in Ag-As-S system glass with high silver content, the voltage inversion method does not Applicable.

Method used

The diffusion process of silver elements in glass was simulated by salt bath treatment method. The diffusion coefficient and diffusion layer thickness of silver elements were measured by scanning electron microscopy and EDS energy spectrum analysis, and the migration ability of silver elements in glass was characterized.

Benefits of technology

Through salt bath treatment and scanning electron microscopy analysis, the impact of glass microstructure on silver migration behavior can be qualitatively analyzed, providing research support for the nucleation process and crystallization performance of photosensitive microcrystalline glass, and is suitable for glass materials with different network structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119269562A_ABST
    Figure CN119269562A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of structural analysis of glass materials, in particular to a method and device for characterizing the migration ability of a silver element in glass, and the method comprises the following steps: carrying out salt bath treatment on a glass sample; testing the glass sample subjected to salt bath treatment to obtain the diffusion coefficient and the diffusion layer thickness of the silver element; the migration ability of the silver element in the glass is represented through the diffusion coefficient of the silver element and the thickness of the diffusion layer. According to the method, the diffusion process of the silver element in the glass is simulated through salt bath treatment, the diffusion coefficient and the diffusion layer depth of the silver element in the glass are obtained through calculation, the method is suitable for glass materials of different network structures, and the influence of the glass microstructure on the silver migration behavior can be qualitatively analyzed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass material structure analysis, and in particular to a method and a device for characterizing the migration ability of silver elements in glass. Background Art

[0002] Photosensitive glass-ceramics is an important component of glass-ceramics, which realizes its photosensitive properties through photosensitizers and nucleating agents in the glass. Specifically, during the exposure process, photons react with sensitizers to release electrons, which are captured by nucleating agents and gradually nucleate and grow during the heat treatment process, providing conditions for crystallization.

[0003] Photothermal refracting glass is a type of photosensitive microcrystalline glass. It is a multi-component, multi-valent co-doped special optical glass containing elements such as cerium, silver, fluorine and bromine. After ultraviolet irradiation and further heat treatment, the irradiated area of ​​the glass will produce small-scale, high-density NaF microcrystals, which will cause the refractive index to decrease and form a refractive index gradient inside the glass. Photothermal refracting glass has excellent refractive ability, laser damage characteristics, optical properties and stable physical and chemical properties. It also has the characteristics of high reliability and easy large-scale production. It is an ideal basic material urgently needed for the development of key technologies such as volume diffraction optical devices, structural optical devices, high-density optical storage media, and high-resolution and high-speed holographic recording media.

[0004] The base glass of the above photosensitive glass-ceramics contains Ce 3+ and Ag + During exposure to UV light, photoelectrons cause Ce 3+ Release electrons and transform to a tetravalent state, while Ag + Captured electrons are converted to Ag 0 . Silver is a nucleating agent for crystallization. Appropriate heat treatment can cause the silver atoms dispersed in the glass to aggregate and nucleate. The nucleation process is a key step in photosensitive microcrystalline glass, which determines its microcrystal precipitation and final performance. The nucleation process is ultimately the aggregation process of silver, which is affected by the migration ability of silver in the glass network. The stronger the silver migration ability, the faster the diffusion rate, and the faster the nucleation, which has an important influence on the number and size of nuclei.

[0005] At present, the research on the migration ability of silver in photosensitive microcrystalline glass and its influence on glass nucleation, as well as the related glass characterization and evaluation methods, have not received much attention. In the Ag-As-S system glass, "Y.Miyamoto, M.Itoh, K.Tanaka, Mobility of Ag ions in Ag-As-S glasses[J], Solid State Communications, 1994, 92(11):895-898." reported that for Ag-As-S glass with a silver content of 15at% to 45at%, a transient ion current was formed in the material by voltage reversal, which characterized the silver migration ability in the material. However, photosensitive microcrystalline glass is a poor conductor of electricity, so this voltage reversal method is not applicable. Therefore, it is necessary to construct a characterization method that can intuitively evaluate the silver migration ability in photosensitive microcrystalline glass to provide support for the research and development of photosensitive microcrystalline glass. Summary of the invention

[0006] The object of the present invention is to provide a method and device for characterizing the migration ability of silver elements in glass, so as to solve the above-mentioned technical problems.

[0007] To achieve the above object, the present invention provides a method for characterizing the migration ability of silver elements in glass, comprising:

[0008] The glass samples were subjected to salt bath treatment;

[0009] The glass samples treated with salt bath were tested to obtain the diffusion coefficient of silver element and the thickness of diffusion layer;

[0010] The migration ability of silver in glass is characterized by the diffusion coefficient of silver and the thickness of the diffusion layer.

[0011] The present invention also provides a device for characterizing the migration ability of silver elements in glass, comprising:

[0012] a treatment unit for subjecting the glass sample to a salt bath treatment;

[0013] An acquisition unit is used to test the glass sample after salt bath treatment to obtain the diffusion coefficient of silver element and the thickness of the diffusion layer;

[0014] Characterization unit, used to characterize the migration ability of silver in glass through the diffusion coefficient of silver and the thickness of diffusion layer.

[0015] Technical effects and advantages of the present invention:

[0016] The present invention simulates the diffusion process of silver element in glass through salt bath treatment, measures the distribution of silver element in glass by scanning electron microscope and EDS energy spectrum analysis, and calculates the diffusion coefficient and diffusion layer depth of silver element in glass. The present invention is suitable for glass materials with different network structures, and can qualitatively analyze the influence of glass microstructure on silver migration behavior. The present invention has important significance in the research of nucleation process, crystallization performance, glass network structure design, nucleation crystallization process design, etc. of silver-containing photosensitive microcrystalline glass.

[0017] Other features and advantages of the present invention will be described in the following description, and partly become obvious from the description, or be understood by implementing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Schematic diagram of the process from salt bath to SEM testing;

[0019] Figure 2 The scanning electron microscope and EDS energy spectrum line scan results of Example A1;

[0020] Figure 3 It is the calculation result of the EDS energy spectrum line scan content of Example A1. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification for people familiar with this technology to understand and read, and are not used to limit the limiting conditions for the implementation of the present invention, so they have no substantial technical significance. Any modification of the structure, change of the proportion relationship or adjustment of the size should still fall within the scope of the technical content disclosed by the present invention without affecting the effects and purposes that can be achieved by the present invention. At the same time, the terms such as "upper", "lower", "left", "right", "middle" and "one" quoted in this specification are only for the convenience of description, and are not used to limit the scope of the implementation of the present invention. The change or adjustment of their relative relationship should also be regarded as the scope of the implementation of the present invention without substantially changing the technical content.

[0023] In order to better understand the present invention, the basic principles of the present invention are briefly introduced:

[0024] The salt bath diffusion in the present invention is different from ion exchange. Conventional ion exchange process is an equivalent exchange reaction, such as immersing glass in high-temperature molten salt, so that the sodium ions on the surface of the glass are exchanged with the potassium ions in the molten salt. In the salt bath process of the present invention, the silver nitrate in the molten salt decomposes to produce zero-valent silver atoms, and the silver atoms participate in the diffusion process.

[0025] The following is a detailed description of the method for characterizing the migration ability of silver element in glass in the present invention. Figure 1 As shown:

[0026] S1. Pre-treat the glass sample.

[0027] Specifically, the glass stress is first eliminated by annealing, followed by cutting, polishing and ultrasonic cleaning in sequence to obtain a glass sample with a clean surface for subsequent use.

[0028] The ultrasonic cleaning time is 10 min to 60 min, preferably 20 min to 30 min.

[0029] Among them, the glass sample is Si-Al-Zn system glass, and the positive valence element components in the glass sample include, by weight percentage: Si: 50%~65%; K: 0.0%~5.0%; Na: 15.0%~35.0%; Zn: 5.0%~15.0%; Al: 2.0%~10.0%; Sn: 0.0%~2.0%; Sb: 0.0%~4.0%; Zr: 0.0%~2.0%; Ag: 0.01%~5.00%; Ce: 0.0%~5.0%. Preferably, Si: 52% to 61%; K: 0.5% to 2.5%; Na: 20.0% to 30.0%; Zn: 6.5% to 12.5%; Al: 3.0% to 8.5%; Sn: 0.0% to 0.7%; Sb: 0.4% to 3.0%; Zr: 0.0% to 1.3%; Ag: 0.04% to 3.10%; Ce: 0.04% to 3.15%.

[0030] S2. Molten salt for salt bath. The molten salt includes AgNO 3 、NaNO 3 .

[0031] In the present invention, AgNO 3 It is the silver source of the diffusion process. AgNO in the molten salt 3 The content is too low, the diffusion source concentration is low, and the diffusion process is slow. When the concentration of silver elements (including silver ions and silver atoms) in the salt bath is lower than the concentration of silver elements in the glass, reverse diffusion may even occur.3 If the content is too high, it will corrode the glass surface. 3 As a molten salt matrix, it can melt at 307°C and transform from solid to liquid, providing salt bath conditions for the diffusion process. 3 Mass percentage content (AgNO 3 The mass percentage of NaNO in the total mass of the molten salt is 0.05% to 5%, preferably 0.05% to 3.5%; 3 Mass percentage content (NaNO 3 The percentage of mass of the molten salt to the total mass of the molten salt) is greater than or equal to 95%, preferably greater than or equal to 96.5%.

[0032] Put the uniformly mixed molten salt into a container and heat it to 400°C to 500°C, preferably 435°C to 475°C, until the molten salt is completely melted and then stir it uniformly.

[0033] S3. Salt bath treatment.

[0034] The salt bath treatment temperature and time will affect the diffusion effect. If the salt bath temperature is too low, the molten salt will melt unevenly and diffuse slowly, which is not conducive to characterization. If the salt bath temperature is too high, the nitrate will decompose violently and diffuse too quickly, which is not conducive to control. In addition, too much silver on the glass surface will squeeze in and destroy the glass network structure. The salt bath time will also affect the diffusion effect of the silver element. If the time is too short, it will not be conducive to the formation of diffusion distribution and cannot be tested. If the salt bath time is too long, the glass surface will corrode.

[0035] Therefore, the salt bath treatment specifically includes: placing the processed glass sample into and immersing it in molten salt, ensuring that the glass sample is immersed in the molten salt, keeping the sample in full contact with the salt all around, and heat-insulating for 0.5h to 5h, preferably 0.5h to 3h.

[0036] S4. Take the sample out of the salt bath, wash the sample after the sample is cooled to room temperature, and then process it, cut a fresh section perpendicular to the surface, polish the section and ultrasonically clean it for 10 minutes to 60 minutes, preferably 20 minutes to 30 minutes.

[0037] S5. Sample scanning electron microscope and EDS spectrum test. Of course, other equipment can also be used as long as the diffusion coefficient of silver and the thickness of the diffusion layer can be determined.

[0038] The polished cross section of the sample was sprayed with gold, and EDS energy spectrum line scanning was performed under a scanning electron microscope to observe the distribution of Ag element content. The line scanning path was kept perpendicular to the natural surface of the glass and parallel to the diffusion path.

[0039] S6. Data processing and calculation.

[0040] The diffusion coefficient and diffusion layer thickness are obtained by calculation based on the EDS energy spectrum data.

[0041] Preferably, this paper uses a SEM scanning electron microscope SU3500 and its EDS spectrometer for measurement. First, the cross section of the glass is sprayed with gold, and then the cross section of the glass is scanned by EDS lines. The scanning path is perpendicular to the natural surface of the glass to obtain the distribution of silver elements in the cross section of the glass.

[0042] The formula for obtaining the diffusion coefficient is:

[0043]

[0044] Among them, C (x,t) Represents the concentration distribution of silver element; C 0 AgNO 3 Concentration; C sub represents the initial concentration of silver in the glass sample; x represents the distance between the silver position and the diffusion interface; t represents the diffusion time of the silver; and D represents the diffusion coefficient of the silver.

[0045] It should be noted that the formula for the diffusion coefficient is derived from the constant source diffusion model in "J. Crank, The Mathematics of Diffusion [M], Oxford university press, 1975.":

[0046] erfc(z)=1-erf(z) (Formula 2)

[0047]

[0048] Among them, C (x,t) is the silver element concentration distribution; x is the distance between the silver element position point and the diffusion interface, t is the silver element diffusion time, C 0 AgNO 3 concentration, D is the diffusion coefficient of silver element, and η is an integral variable used for mathematical calculations and has no specific physical meaning.

[0049] In order to better illustrate the present solution, embodiments are provided below.

[0050] Tables 1 to 3 show the characteristics of migration ability in different glasses obtained by the method of the present invention. In addition, the tables also list the positive-valence element composition in the glass and the corresponding test results. In this specification, unless otherwise specified, the content of each positive-valence element component is the weight percentage of the weight of the positive-valence element component to the total weight of all positive-valence element components.

[0051] Table 1 Experimental data table of the embodiment

[0052]

[0053]

[0054]

[0055] Table 2 Experimental data table of the embodiment

[0056]

[0057]

[0058] Table 3 Experimental data table of the embodiment

[0059]

[0060]

[0061] According to the contents in the table, in Example A1, Example A2, and Example A3, glass samples with different Zn and Al content are designed, and the migration rate and diffusion layer thickness of the silver element in each different glass network can be obtained by using the migration ability characterization method of the silver element in the glass of the present invention, so as to achieve the characterization and evaluation of the migration ability of the silver element in the matrix, such as Figure 2-3 At the same time, the increase of Zn and Al content in the glass will make the glass network structure more compact. 3+ The influence of components is stronger than that of Zn 2+ As a result, the migration ability of the silver element in the glass will be weakened, the diffusion coefficient will be reduced, and the thickness of the diffusion layer will be reduced. This conclusion can also be confirmed by Examples A1, A2 and A3.

[0062] Embodiment A4, Embodiment A5, Embodiment A6 are glass samples with different Si and Na content designed to implement the migration ability characterization method of silver element in glass of this patent. 4+ Plays the role of glass network forming a network, Na + It will have the effect of breaking the network. The increase in the Na / Si element ratio will destroy the tightness of the glass network structure, which is beneficial to the migration of silver elements. The migration ability of silver elements in the glass is enhanced, the diffusion coefficient increases, and the thickness of the diffusion layer becomes thicker.

[0063] Embodiment A7 and Embodiment A8 are designed to implement the method for characterizing the migration ability of silver in glass of this patent with glass samples containing or not containing Zr element, and the migration rate and diffusion layer thickness of silver element in different glass networks can be obtained, so as to realize the characterization and evaluation of the migration ability of silver element in glass matrix, as shown in the results in Table 2. Zr 4+Located in the gaps of the glass network, it has the effect of preventing the migration of silver elements in the glass, thereby weakening the migration ability of silver elements in the glass, reducing the diffusion coefficient and the thickness of the diffusion layer.

[0064] Embodiment A9, Embodiment A10, Embodiment A11, Embodiment A12, Embodiment A13, Embodiment A14, Embodiment A15 design different contents of silver nitrate in salt baths, implement the migration ability characterization method of silver element in glass of this patent, and obtain the migration rate of silver element and the thickness of diffusion layer of glass in salt baths with different silver element concentrations, as shown in the results of Table 2 and Table 3. The higher the content of silver nitrate in the salt bath, the more sufficient the diffusion source of silver element, the greater the concentration difference of silver element in the salt bath environment and the glass matrix, the stronger the driving force for the diffusion process of silver element, and thus the migration ability of silver element in glass will be enhanced, the diffusion coefficient will increase, and the thickness of diffusion layer will increase.

[0065] The present invention also provides a device for characterizing the migration ability of silver elements in glass, comprising:

[0066] a treatment unit for subjecting the glass sample to a salt bath treatment;

[0067] An acquisition unit is used to test the glass sample after salt bath treatment to obtain the diffusion coefficient of silver element and the thickness of the diffusion layer;

[0068] Characterization unit, used to characterize the migration ability of silver in glass through the diffusion coefficient of silver and the thickness of diffusion layer.

[0069] Since the content protected by this device is similar to that protected by the above method, no further introduction will be given here. Please refer to the discussion section of the above method for details.

[0070] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for characterizing the migration ability of silver elements in glass, characterized in that: include: The glass samples were subjected to salt bath treatment; The glass samples treated with salt bath were tested to obtain the diffusion coefficient of silver element and the thickness of diffusion layer; The migration ability of silver in glass is characterized by the diffusion coefficient of silver and the thickness of the diffusion layer.

2. The method according to claim 1, characterized in that The glass samples after salt bath treatment were tested by scanning electron microscope and EDS spectrometer.

3. The method according to claim 1, characterized in that Before subjecting the glass sample to the salt bath treatment, the method further includes: pre-treating the initial glass sample; Wherein, the pretreatment includes: annealing, cutting, polishing and ultrasonic cleaning.

4. The method according to claim 3, characterized in that The ultrasonic cleaning time is 10 minutes to 60 minutes.

5. The method according to claim 1, characterized in that Salt bath treatment of glass samples, including: Weigh the molten salt and place it in a container, and heat the container to completely melt the molten salt and mix it evenly; At the same temperature, the glass sample is immersed in a container and kept warm.

6. The method according to claim 5, characterized in that The molten salt comprises: AgNO3 with a mass fraction of 0.05% to 5% and NaNO3 with a mass fraction of ≥95%.

7. The method according to claim 5, characterized in that The temperature at which the container is heated is 400°C to 500°C.

8. The method according to claim 5, characterized in that The insulation time is 0.5h to 5h.

9. The method according to claim 1, characterized in that: The method further comprises: Cooling and cleaning the glass sample after the salt bath treatment, and cutting a fresh section perpendicular to the surface of the glass sample; Scanning electron microscopy and EDS energy spectrum testing were performed on the fresh section after polishing and secondary cleaning.

10. The method according to claim 9, characterized in that The secondary cleaning is ultrasonic cleaning and the cleaning time is 10 to 60 minutes.

11. The method according to claim 6, characterized in that The diffusion coefficient is obtained by the following formula: Among them, C (x,t) represents the concentration distribution of silver element; C0 represents the concentration of AgNO3; C sub represents the initial concentration of silver in the glass sample; x represents the distance between the silver position and the diffusion interface; t represents the diffusion time of the silver; and D represents the diffusion coefficient of the silver.

12. The method according to claim 2, characterized in that: The thickness of the diffusion layer is the depth from the surface of the glass sample to the point where the silver content in the glass sample reaches the baseline level according to the scanning electron microscope (EDS) energy spectrum line scan result.

13. The method according to claim 1, characterized in that The glass sample is Si-Al-Zn system glass.

14. The method according to claim 1, characterized in that In terms of weight percentage, the positive-valence element components in the glass sample include: Si: 50% to 65%; K: 0.0% to 5.0%; Na: 15.0% to 35.0%; Zn: 5.0% to 15.0%; Al: 2.0% to 10.0%; Sn: 0.0% to 2.0%; Sb: 0.0% to 4.0%; Zr: 0.0% to 2.0%; Ag: 0.01% to 5.00%; Ce: 0.0% to 5.0%.

15. The method according to claim 1, characterized in that In terms of weight percentage, the positive-valence element components in the glass sample include: Si: 52% to 61%; K: 0.5% to 2.5%; Na: 20.0% to 30.0%; Zn: 6.5% to 12.5%; Al: 3.0% to 8.5%; Sn: 0.0% to 0.7%; Sb: 0.4% to 3.0%; Zr: 0.0% to 1.3%; Ag: 0.04% to 3.10%; Ce: 0.04% to 3.15%.

16. A device for characterizing the migration ability of silver elements in glass, characterized in that: include: a treatment unit for subjecting the glass sample to a salt bath treatment; An acquisition unit is used to test the glass sample after salt bath treatment to obtain the diffusion coefficient of silver element and the thickness of the diffusion layer; Characterization unit, used to characterize the migration ability of silver in glass through the diffusion coefficient of silver and the thickness of diffusion layer.

Citation Information

Cited By

  • Method for detecting migration ability of metal elements in glass matrix

    CN120577169A

  • Method for detecting migration ability of metal elements in glass matrix

    CN120577169B